The Determinant Factors of Technology Adoption for Improving Firm’s Performance: An Empirical Research of Indonesia’s Electricity Company - Zainal Arifin; Firmanszah .; Avanti Fontana; Setyo Hari Wijayanto (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2016)
This study investigates the determinant factors of technology adoption by connecting Technology Organizational Environment (TOE) with the dynamic capability factors. Using 518 respondents representing 222 business units of Indonesia’s electricity company, the study found that only the absorptive capability has a positively significant effect on technology adoption. Practically, the study emphasizes that without the absorptive capability for managing the resource, the core competence of a firm will not occur and the adoption of technology will be less effective. Another finding is the absorptive capability’s typology mapping the eight technology adoption statuses in an organization, based on three of the determinant factors: the externalities, entrepreneurial leadership and slack resources.